Molecular imprinting of cyclodextrin in homogeneous solutions - Takayuki Hishiya; Tomohiro Akiyama; Hiroyuki Asanuma; Makoto Komiyama (ՀՀ ԳԱԱ հրատ.)
In homogeneous and alkaline aqueous solutions, cyclodesxtrin was reacted with epichlorohydrin in the presence of various templates.
Keywords: Biology; Biotechnology